Overcoming the crisis caused by COVID-19 and its post-crisis impact by tourism in Portugal - Ferreira, Fernanda A. (2022)
Purpose - Tourism in Portugal has been growing exponentially in recent years, with a significant impact on the national economy. However, this growth was restricted by the current health crisis, caused by COVID-19. The pandemic has resulted in the confinement of a large part of the world’s population; the cancellation of travel; the closure of most establishments, including those involved in the tourism sector; the increase in the unemployment rate; and other tragic repercussions.The objective of the study is to understand the changes made by the sector to defeat this crisis and predict the most significant modifications in the sector and its impact. Design/methodology - Quantitative research based on a questionnaire survey, which target was the population of employees of tourism enterprises in Portugal. Qualitative research based on data collected in official governments websites, Turismo de Portugal I.P. website and national statistical data websites. Findings - This paper studies the measures implemented by the Portuguese Government and the tourist impact in the economy during the pandemic. It also examines the advantages and disadvantages of the implementation of those measures and how economic recovery is being achieved. From the results of the investigation, it was possible to conclude tourism enterprises generally suffered a considerable impact from the crisis caused by COVID-19. For this reason, they have taken various measures to ensure security conditions for all guests and staff. From the respondents’ answers it is possible to perceive the discontent of the workers with the lack of help from the Portuguese Government.